1989
DOI: 10.3382/ps.0680501
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Concurrent Stressors in Chicks.

Abstract: Effects of multiple concurrent stressors on Hubbard x Hubbard chicks (Days 10 to 17 posthatch) were studied in a 2(6)-factorial experiment that employed as treatments aerial ammonia (A, 0 or 125 ppm), beak trimming (B, sham handled or beak trimmed/cauterized), coccidiosis (X, gavage with 0 or 6x10(5) sporulated Eimeria acervulina oocysts), intermittent electric shock (E, 0 or between 2.9 and 8.7 mA), heat stress (H, 30.4 or 34.8 C) and continuous noise (N, 80 or 95 dB). All stressors, except noise, decreased w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 10 publications
2
28
0
Order By: Relevance
“…NH 3 in poultry houses also affects immunological function, reducing specific antibody titers (Caveny et al, 1981) and increasing disease susceptibility (Beker et al, 2004). Moreover, the effects of NH 3 and other simultaneous stressors are generally additive (McFarlane et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…NH 3 in poultry houses also affects immunological function, reducing specific antibody titers (Caveny et al, 1981) and increasing disease susceptibility (Beker et al, 2004). Moreover, the effects of NH 3 and other simultaneous stressors are generally additive (McFarlane et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Some acute events, in addition to physical restraint, have been shown to induce a stress response in chickens, for example heat stress [27][28][29] and unpredictable light regimes [30]. Restraint stress however is a well-established method for triggering a stress response in chickens (see for example [29,31,32] ) where also the HPA-axis recovery has been investigated [31].…”
Section: Introductionmentioning
confidence: 99%
“…Because HP chicks showed shorter durations of immobility and less anxiety-related behaviour in this situation than LP birds (Marin et al, 1997a) it is conceivable that they have lower underlying fearfulness. Fear is a potent stressor, growing birds are routinely exposed to a variety of potentially frightening events which frequently depress weight gain (McFarlane et al, 1989), and negative relationships between fearfulness and growth have been reported in domestic chicks and Japanese quail (Mauldin and Siegel, 1979;Bessei, 1984;Gross et al, 1984;Jones, 1996;Jones et al, 1997). Thus, rather than showing a series of acute stress responses to frightening stimuli, with their known catabolic effects (Hemsworth et al, 1994), HP chicks might be more likely to utilise resources for coping with other environmental stressors or for growth.…”
Section: Discussionmentioning
confidence: 96%
“…It is generally accepted that exposure to multiple and/or chronic stressors can seriously compromise the performance as well as the welfare of poultry (McFarlane et al, 1989;Zulkifli and Siegel, 1995;Jones, 1996). For example, disruption of the social environment or the elicitation of intense or prolonged fear can cause panic-related injuries, pain or death and reduce growth, food conversion efficiency, egg production and product quality (Gross et al, 1984;Mills and Faure, 1990;Gross and Siegel, 1993;Rosales, 1994;Jones, 1996;1997).…”
Section: Introductionmentioning
confidence: 96%